Knowledge, awareness and prevention of cervical cancer among women attending a rural based tertiary care centre, Theni, South India - Sambath, Shanthadevi; Chandrasekaran, Madhumitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Cervical carcinoma is the most common genital cancer in India and a leading cause of cancer-associated deaths. Cervical cancer is both preventable and curable, yet morbidity and mortality from the disease remain high especially in developing countries. Request for cervical cancer screening is exceedingly low among women due to lack of awareness of cervical cancer and the screening methods Methods: A cross sectional study was conducted in 200 women attending Gynaecology OPD in Government Theni Medical College Hospital, Tamil Nadu. We studied the knowledge, awareness, and attitude of patients, about cervical cancer and the screening methods in a tertiary institution. They were interviewed with predesigned questionnaire after getting informed consent. Results: Of the 200 patients surveyed, 74 (37%) had heard of cervical cancer, while 44 (22%) knew about screening, with health care providers being their most frequent source of information. Only 26 (13%) women ever had screening done and no one is aware of HPV vaccine. Conclusions: Adequate health information and counselling on cervical cancer and regular screening still need to be emphasized in developing countries so as to reverse the morbidity and mortality associated with cervical cancer.